Ecclesiology and governance. J. Ratzinger and W. Kasper’s debate on the relationship between the universal church and the local church - Martínez Gordo, Jesús (Revista Latinoamericana de teología, 2005)
No abstract available. Revista latinoamericana de teología, Vol. 22, No. 66, 2005: 229-250.